Antibiofilm Effects of Nanoparticles and Visible Light Illumination Against Listeria monocytogenes - Puranen, Sanna; Riekkinen, Kati; Korhonen, Jenni (Frontiers in Microbiology, 2021)
Listeria monocytogenes bacteria pose a particular risk to the food industry as the species is known to form biofilm and to survive in a wide range of challenging environmental conditions. L. monocytogenes can cause listeriosis, a serious food-borne disease, and effective and safe antibiofilm materials and sanitary methods for food processing environments are intensively sought. A variety of nanoparticle materials have been recognized as safe to use in food environments, which allows the application of nanomaterials also for food safety purposes. Nanoparticles together with light illumination generate reactive oxygen species which inactivate bacteria by breaking down cell membranes, proteins, and DNA. The main objective of this study was to evaluate the efficacy of nanomaterials and blue light illumination for L. monocytogenes ATCC 7644 biofilm inactivation. Biofilm was allowed to form for 72 h on nanocoated stainless steel and aluminum plates, after which the plates were illuminated. Non-coated control plates were used to evaluate the antibiofilm efficacy of nanocoating. Plate count method was used to evaluate bacteria counts after illumination. Nanocoating did not affect initial biofilm formation compared to the control plates. Biofilm was significantly (p < 0.05) reduced on stainless steel, aluminum, and TiO2-coated aluminum plates after 72-h illumination by 1.9, 3.2, and 5.9 log, respectively. Nanocoating with visible light illumination could be an effective and safe method for enhancing food safety in food processing facilities to control biofilm formation. Evidence of antibiofilm properties of nanomaterials together with visible light illumination is limited; hence, future studies with variable light intensities and nanomaterials are needed.